A Framework To Analyse The Efficiency Of Baitul Maal wa Tamwil (BMT) As Islamic Microfinance Institutions in Indonesia - Atiqi Chollisni Nasution (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2013)
This paper aims to present a conceptual model on the efficiency of BMT asIslamic microfinance institutions in Indonesia. In the last twenty years, thegrowth of BMTs increase significantly and have contributed positively to thedevelopment of socio economic of the country. Recently, there are around4,000 BMTs operate and have enhanced thousand poor people life. BMTsresponsible in collecting, managing and distributing the funds either forcharity or providing financial services for the poor. The paper identifies theappropriate methods to evaluate efficiency of BMTs, such evaluation ofIslamic microfinance institution to function effectively to achieve socioeconomic objective. The findings are not only relevant and applicable toIndonesia but also to other muslim countries and would be useful for furtherempirical research in this area.